Enhanced methane production by semi-continuous mesophilic co-digestion of potato waste and cabbage waste: Performance and microbial characteristics analysis. (July 2017) - Mu, Hui; Zhao, Chunhui; Zhao, Yuxiao; Li, Yan; Hua, Dongliang; Zhang, Xiaodong; Xu, Haipeng
Highlights: Cabbage waste was co-digested with potato waste for efficient biomethanation. Highest methane yield of 360 mL/g-VS was obtained at an OLR of 5.0 kg VS/m 3 ·d. Application of anaerobic granular sludge as an inoculum. The dominant acetoclastic methanogen Methanosaeta decreased largely. Increments of Methanosarcina and Methanobacterium led to the increased methane. Abstract: Anaerobic granular sludge was used as an inoculum for co-digestion of potato waste (PW) and cabbage waste (CW) in batch and semi-continuous modes at 37 ± 1 °C for enhanced methane generation. Batch test results indicated that an equal proportion (1:1) by volatile solid was the optimal mixing ratio for co-digestion of PW and CW. Semi-continuous co-digestion process results showed that the stepwise increasing of the organic loading rates from 1.0 to 5.0 kg VS/m 3 ·d improved the methane yield from 224 to 360 mL/g-VS. And the highest value was respectively 18.4% and 24.1% higher as compared to the mon-digestion of PW and CW. Further investigation with high-throughput sequencing analysis revealed that the enhanced methane generation was attributed to the partial shift from archaeal Methanosaeta to Methanosarcina and Methanobacterium, and from bacterial Firmicutes to Bacteroidetes and Proteobacteria . The volatile fatty acids concentration accounted for the modification of microbial communities.